Glass substrate and manufacturing method thereof
Patent Information
- Application Number
- JP2023133306
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-03-03
AI Technical Summary
【0020】 本発明によれば、表面の触り心地や、ペンによる書き心地を効果的に向上させ得る、ガラス基板及び該ガラス基板の製造方法を提供することができる。
Smart Images

Figure 2025028471000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass substrate having an uneven surface and a method for manufacturing the glass substrate. [Background technology]
[0002] In recent years, attempts have been made to improve the feel of the surface and the writing comfort with a pen by imparting irregularities to the surface of glass substrates used for displays, housings, doors, and the like of electronic devices.
[0003] For example, the following Patent Document 1 discloses a glass substrate for a pen input device that is disposed on the front side of a display device in the pen input device. Patent Document 1 describes that the glass substrate has irregularities on at least one main surface, and that the maximum valley depth Rv of the roughness curve on the main surface having irregularities is 10 nm or more and 400 nm or less, and the average length RSm of the roughness curve is 500 nm or more and 2000 nm or less. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-20942 A Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, preferences for the feel of the surface of a glass substrate and the writing comfort when inputting characters on the surface of the glass substrate vary depending on the person and the application. For example, when touching a glass substrate, it may be preferable for the surface of the glass substrate to have a strong grip. Also, when inputting characters on the surface of the glass substrate with a pen, it may be preferable for the surface to have a strong writing comfort (wherein the strength of friction is directly transmitted). However, the unevenness of the surface as described in Patent Document 1 has a relatively smooth feel, and it may be difficult to sufficiently improve the feel of the surface of the glass substrate and the writing comfort with a pen.
[0006] An object of the present invention is to provide a glass substrate that can effectively improve the feel of the surface to the touch and the feel of writing with a pen, and a method for manufacturing the glass substrate. [Means for solving the problem]
[0007] Various aspects of a glass substrate and a method for manufacturing the glass substrate that solves the above problems will be described below.
[0008] A glass substrate according to a first aspect of the present invention is a glass substrate having a concave-convex portion on its surface and an unprocessed portion that has not been processed to provide the concave-convex portion, wherein the concave-convex portion has an arithmetic mean height Sa of 1 nm or more and 100 nm or less in a 74 μm × 55 μm area when the cutoff value of a high-pass filter λc is 14 μm and the cutoff value of a low-pass filter λs is 0.35 μm, the concave-convex portion contains at least one component selected from the group consisting of Al, Zr, and Si, and the difference between the total mass percentage of Al, Zr, and Si in any 100 μm square area of the concave-convex portion and the total mass percentage of Al, Zr, and Si in any 100 μm square area of the unprocessed portion is 0.1 mass % or more.
[0009] A glass substrate according to a second aspect of the present invention is a glass substrate having an uneven surface and an unprocessed portion that has not been processed to provide the uneven surface, wherein the uneven surface has an arithmetic mean height Sa of 1 nm or more and 100 nm or less in an area of 74 μm x 55 μm when the cutoff value of a high-pass filter λc is 14 μm and the cutoff value of a low-pass filter λs is 0.35 μm, and the uneven surface is compounded with particles containing at least one of Al, Zr, and Si.
[0010] In the glass substrate of aspect 3, in aspect 1 or aspect 2, both the concave-convex portion and the non-processed portion may be provided on one main surface of the glass substrate.
[0011] In the glass substrate of aspect 4, in aspect 3, the glass substrate may have a first main surface and a second main surface opposing each other, the first main surface of the glass substrate may be provided with the uneven portion, and the second main surface of the glass substrate may be provided with the unprocessed portion.
[0012] In the glass substrate of aspect 5, in any one of aspects 1 to 4, it is preferable that the difference between the total mass percentage of Al, Zr, and Si in any 100 μm square area of the uneven portion and the total mass percentage of Al, Zr, and Si in any 100 μm square area of the non-processed portion is 10 mass % or less.
[0013] In the glass substrate of aspect 6, in any one of aspects 1 to 5, the glass substrate is preferably made of silicate glass.
[0014] In the glass substrate of aspect 7, in any one of aspects 2 to 6, the particles are preferably at least one type of particles selected from the group consisting of aluminum oxide, aluminum nitride, aluminum carbide, aluminum silicate, zirconium oxide, yttria-stabilized zirconia, zircon, silicon oxide, and silicon nitride.
[0015] In the glass substrate of embodiment 8, in any one of embodiments 2 to 7, the average particle size of the particles is preferably 0.1 μm or more and 10 μm or less.
[0016] In the glass substrate of embodiment 9, in any one of embodiments 2 to 8, the purity of the particles is preferably 90% or more.
[0017] A glass substrate manufacturing method according to aspect 10 of the present invention is a glass substrate manufacturing method according to any one of aspects 1 to 9, and is characterized in that it includes a step of preparing an original glass substrate and a step of subjecting the original glass substrate to a blasting treatment, and the treatment pressure during the blasting treatment is 0.1 MPa or more and 3.0 MPa or less.
[0018] The glass substrate manufacturing method of Aspect 11 preferably further includes a step of subjecting the original glass substrate that has been subjected to the blasting treatment to a heat treatment in accordance with Aspect 10.
[0019] In the method for producing a glass substrate of the twelfth aspect, in the eleventh aspect, the heat treatment temperature during the heat treatment is preferably 100° C. or higher and the glass transition temperature of the original glass substrate or lower. Effect of the Invention
[0020] According to the present invention, it is possible to provide a glass substrate and a method for manufacturing the glass substrate, which can effectively improve the feel of the surface to the touch and the feel when writing with a pen. [Brief description of the drawings]
[0021] [Figure 1] 1 is a schematic cross-sectional view showing a glass substrate according to one embodiment of the present invention. [Diagram 2] FIG. 13 is a schematic cross-sectional view showing a glass substrate of a modified example. [Diagram 3] 13 is a diagram for explaining a measured cross-sectional curve of unevenness in a modified example. FIG. [Figure 4] 1 is a scanning electron microscope photograph showing the uneven portion of the glass substrate of Example 4. [Diagram 5] 5 is a scanning electron microscope photograph showing an enlarged view of a portion in FIG. 4 where alumina particles are provided. [Figure 6] 2 is a scanning electron microscope photograph showing the surface of the glass substrate of Comparative Example 1. [Figure 7] 1 is a scanning electron microscope photograph showing the uneven portion of the glass substrate of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Preferred embodiments will be described below. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments. In addition, in each drawing, components having substantially the same functions may be referred to by the same reference numerals.
[0023] [Glass substrate] FIG. 1 is a schematic cross-sectional view showing a glass substrate according to one embodiment of the present invention.
[0024] 1, the glass substrate 1 has a rectangular flat plate shape. However, the shape of the glass substrate 1 is not particularly limited, and may be a flat plate shape having a circular or polygonal outline, a flat plate shape that is entirely curved, a spherical or aspherical lens shape, or the like.
[0025] The material of the glass substrate 1 is not particularly limited, but examples thereof include silicate-based glasses such as aluminosilicate glass, alkali-containing aluminosilicate glass, borosilicate glass, lithium silicate glass, and soda-lime silicate glass. Here, silicate-based glass refers to glass containing 10 mass % or more of SiO2 as a glass composition.
[0026] The glass substrate 1 has a first main surface 1a and a second main surface 1b facing each other. The first main surface 1a and the second main surface 1b are the surfaces of the glass substrate 1. In this embodiment, a concave-convex portion 2 is provided in a part of the first main surface 1a of the glass substrate 1. The first main surface 1a of the glass substrate 1 also has a non-processed portion 3 that is not processed to provide the concave-convex portion 2. In this embodiment, the entire second main surface 1b of the glass substrate 1 is also the non-processed portion 3 that is not processed to provide the concave-convex portion 2. However, in the present invention, the concave-convex portion 2 may also be provided on the second main surface 1b of the glass substrate 1.
[0027] In the present invention, it is sufficient that the uneven portion 2 is provided on at least a part of the first main surface 1a of the glass substrate 1. The uneven portion 2 is preferably provided on 1% or more of the area of the first main surface 1a of the glass substrate 1, more preferably on 30% or more, and further preferably on 50% or more.
[0028] Fig. 2 is a schematic cross-sectional view showing a modified glass substrate. As in the glass substrate 10 shown in Fig. 2, the concave-convex portion 2 may be provided on the entire first main surface 1a of the glass substrate 10. In this case, it is sufficient that the non-processed portion 3 is provided on at least a part of the second main surface 1b of the glass substrate 10. Hereinafter, the modified glass substrates 10 will be collectively referred to as glass substrate 1.
[0029] The thickness of the glass substrate 1 is not particularly limited, and can be, for example, 30 μm or more and 5 mm or less.
[0030] In this embodiment, the uneven portion 2 of the glass substrate 1 has an arithmetic mean height Sa of 1 nm or more and 100 nm or less in an area of 74 μm × 55 μm, when the cutoff value of the high-pass filter λc is 14 μm and the cutoff value of the low-pass filter λs is 0.35 μm. Since the arithmetic mean height Sa of the uneven portion 2 of the glass substrate 1 of this embodiment is within the above range, the surface (uneven portion 2) is excellent in feel and writing comfort with a pen.
[0031] The arithmetic mean height Sa of the uneven portion 2 of the glass substrate 1 is preferably 2 nm or more, more preferably 3 nm or more, even more preferably 4 nm or more, even more preferably 5 nm or more, even more preferably 10 nm or more, even more preferably 15 nm or more, particularly preferably 20 nm or more, and is preferably 98 nm or less, more preferably 97 nm or less, even more preferably 96 nm or less, even more preferably 95 nm or less, even more preferably 90 nm or less, even more preferably 85 nm or less, and particularly preferably 80 nm or less.
[0032] When the arithmetic mean height Sa of the uneven portion 2 of the glass substrate 1 is equal to or greater than the above lower limit, the feel of the surface of the glass substrate 1 to the touch and the feel of writing with a pen can be further improved. When the arithmetic mean height Sa of the uneven portion 2 of the glass substrate 1 is equal to or less than the above upper limit, the visibility of an image displayed on the glass substrate 1 can be further improved. In this case, the uneven portion 2 of the glass substrate 1 is not too rough, and the feel of the surface of the glass substrate 1 to the touch and the feel of writing with a pen can be further improved.
[0033] The "arithmetic mean height Sa" is a parameter defined by ISO 25178, which is a parameter obtained by expanding a measured cross-sectional curve showing the cross-sectional shape of unevenness to a surface. Specifically, the arithmetic mean height Sa can be calculated from the average of the absolute values of the heights Zn of each point relative to the average surface of the surface in a specified three-dimensional region (Sa=(Σ|Zn|) / n). In the present invention, the measurement is performed in an area of 74 μm×55 μm, and the arithmetic mean height Sa is calculated by setting the cutoff value of the high-pass filter λc to 14 μm and the cutoff value of the low-pass filter λs to 0.35 μm.
[0034] In the first invention of the present application, the uneven portion 2 of the glass substrate 1 contains at least one component selected from the group consisting of Al, Zr, and Si. In addition, in the glass substrate 1, the difference between the total mass percentage of Al, Zr, and Si in any 100 μm square area of the uneven portion 2 and the total mass percentage of Al, Zr, and Si in any 100 μm square area of the non-processed portion 3 is 0.1 mass % or more.
[0035] The total mass ratio of Al, Zr, and Si in any 100 μm square range can be determined by performing elemental analysis in any 100 μm square range, for example, by scanning electron microscope energy dispersive X-ray spectroscopy (SEM-EDX). It is preferable to perform elemental analysis in any 100 μm square range at multiple measurement points and determine the mass ratio of each component from the average value. In the examples described below, elemental analysis is performed in a 100 μm square range at five arbitrary points on each of the uneven portion (processed portion) and the non-processed portion, and the average value is used as the mass ratio of each component.
[0036] In the second invention of the present application, the uneven portion 2 of the glass substrate 1 is compounded with particles containing at least one of Al, Zr, and Si.
[0037] The phrase "particles containing at least one of Al, Zr, and Si are composited in the uneven portion 2 of the glass substrate 1" means that particles containing at least one of Al, Zr, and Si are in a compound or mixture state in the uneven portion 2 of the glass substrate 1. For example, whether or not the particles are composited can be confirmed by observing using a scanning electron microscope (SEM) and performing elemental analysis of the observed particles by SEM-EDX.
[0038] Hereinafter, the first and second inventions may be collectively referred to as the present invention. The first and second inventions may be implemented alone or in combination.
[0039] Since the glass substrate 1 of the present embodiment has the above-mentioned configuration, it is possible to effectively improve the feel of the surface of the glass substrate 1 and the feel of writing with a pen. This can be explained as follows.
[0040] Preferences for the feel of the surface of a glass substrate and the writing comfort when inputting characters on the surface of the glass substrate vary depending on the person and the application. For example, when touching a glass substrate, it may be preferable for the surface of the glass substrate to have a strong grip. Also, when inputting characters on the surface of a glass substrate with a pen, it may be preferable for the surface of the glass substrate to have a strong writing comfort (wherein the strength of friction is directly transmitted). However, the unevenness formed by applying a blasting treatment or an etching treatment to the surface of a glass substrate using a conventional method has a strong smooth feel, and there are cases where the feel of the surface of the glass substrate and the writing comfort are not sufficiently improved.
[0041] In contrast, in the first invention of the present application, the difference between the total mass percentage of Al, Zr, and Si in any 100 μm square area of the uneven portion 2 and the total mass percentage of Al, Zr, and Si in any 100 μm square area of the non-processed portion 3 is 0.1 mass % or more, so that the uneven portion 2 of the glass substrate 1 can be given a strong grip, and the feel of the surface of the glass substrate 1 and the feel of writing with a pen can be effectively improved. This point can be explained as follows.
[0042] In glass substrate 1, the difference between the total mass percentage of Al, Zr, and Si in any 100 μm square range of uneven portion 2 and the total mass percentage of Al, Zr, and Si in any 100 μm square range of non-processed portion 3 is 0.1 mass % or more, and therefore it is believed that particles containing at least one selected from the group consisting of Al, Zr, and Si are present in uneven portion 2 of glass substrate 1. The presence of these particles can provide strong grip to uneven portion 2 on the surface of glass substrate 1, effectively improving the feel of the surface of glass substrate 1 and the feel of writing with a pen.
[0043] Furthermore, in the second invention of the present application, particles containing at least one of Al, Zr, and Si are compounded in the uneven portion 2, and the presence of these particles can provide a strong grip to the uneven portion 2 on the surface of the glass substrate 1, effectively improving the feel of the surface of the glass substrate 1 and the feel of writing with a pen.
[0044] In this embodiment, the difference between the total mass proportion of Al, Zr, and Si in any 100 μm square area of the uneven portion 2 and the total mass proportion of Al, Zr, and Si in any 100 μm square area of the non-processed portion 3 is preferably 0.11 mass% or more, more preferably 0.12 mass% or more, even more preferably 0.13 mass% or more, particularly preferably 0.14 mass% or more, and is preferably 10 mass% or less, more preferably 9 mass% or less, even more preferably 8 mass% or less, and particularly preferably 7 mass% or less.
[0045] When the difference in mass ratio between the concave-convex portion 2 and the non-processed portion 3 is equal to or greater than the lower limit, it is possible to more effectively improve the feel of the surface of the glass substrate 1 and the writing comfort with a pen. Similarly, when the difference in mass ratio between the concave-convex portion 2 and the non-processed portion 3 is equal to or less than the upper limit, it is possible to more effectively improve the feel of the surface of the glass substrate 1 and the writing comfort with a pen.
[0046] In addition, whether the glass composition of the glass substrate 1 itself contains Al, Zr, and Si, or does not contain any or all of Al, Zr, and Si, the difference between the total mass proportion of Al, Zr, and Si in any 100 μm square area of the uneven portion 2 and the total mass proportion of Al, Zr, and Si in any 100 μm square area of the non-processed portion 3 can be calculated in the same way.
[0047] In this embodiment, the total mass proportion of Al, Zr, and Si in any 100 μm square area of the uneven portion 2 is preferably 30 mass% or more, more preferably 35 mass% or more, even more preferably 40 mass% or more, and is preferably 95 mass% or less, more preferably 90 mass% or less, even more preferably 85 mass% or less.
[0048] When the mass proportion of the uneven portion 2 is equal to or greater than the lower limit, it is possible to more effectively improve the feel of the surface of the glass substrate 1 and the writing comfort with a pen. Similarly, when the mass proportion of the uneven portion 2 is equal to or less than the upper limit, it is possible to more effectively improve the feel of the surface of the glass substrate 1 and the writing comfort with a pen.
[0049] The uneven portion 2 of the glass substrate 1 is preferably composed of particles (hereinafter, sometimes simply referred to as particles) containing at least one selected from the group consisting of Al, Zr, and Si, more preferably composed of particles containing at least one of Al and Zr, and even more preferably composed of particles containing Al.
[0050] Examples of the particles containing Al include particles of aluminum oxide (alumina), aluminum nitride, aluminum carbide, aluminum silicate, etc. Among these, the particles containing Al are preferably alumina particles such as α-alumina having high crystallinity.
[0051] Examples of particles containing Zr include particles of zirconium oxide, yttria-stabilized zirconia, zircon, and the like.
[0052] Examples of particles containing Si include particles of silicon oxide, silicon nitride, silicon carbide, and the like.
[0053] These particles may be used alone or in combination of two or more kinds.
[0054] The Mohs hardness of the particles is preferably 4.0 or more, more preferably 4.5 or more, and even more preferably 5.0 or more. In this case, it is possible to provide a stronger grip to the uneven portion 2 of the glass substrate 1, and it is possible to more effectively improve the feel of the surface of the glass substrate 1 and the feel of writing with a pen. The upper limit of the Mohs hardness of the particles is not particularly limited, and can be, for example, 10.
[0055] Examples of the shape of the particles include angular, needle-like, polyhedral, crushed, irregular, substantially spherical, etc. Among them, from the viewpoint of providing a stronger grip on the unevenness 2 of the glass substrate 1 and facilitating compounding of the particles with the unevenness 2 of the glass substrate 1, the particles are preferably polyhedral.
[0056] The purity of the particles is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. When the purity of the particles is equal to or more than the above lower limit, the transparency of the uneven portion 2 of the glass substrate 1 can be further improved. Therefore, the purity of the particles may be 100%. The purity of the particles is the purity of at least one element selected from the group consisting of Al, Zr, and Si.
[0057] The average particle size of the particles is preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.3 μm or more, and is preferably 10 μm or less, more preferably 9 μm or less, even more preferably 8 μm or less. When the average particle size of the particles is equal to or less than the above upper limit, the transparency of the uneven portion 2 of the glass substrate 1 can be further improved. Furthermore, when the average particle size of the particles is within the above range, the touch of the surface of the glass substrate 1 and the writing comfort with a pen can be further effectively improved.
[0058] In this specification, the average particle diameter can be measured, for example, by observing particles in the uneven portion 2 with a scanning electron microscope. For example, the projected area circle equivalent diameter of all particles observed in any 100 μm square area of the uneven portion 2 is measured with image analysis software (manufactured by Hitachi High-Tech Corporation, software attached to S3400 SEM-EDX) to obtain the average particle diameter.
[0059] In this embodiment, the average length RSm of the roughness curve element in the uneven portion 2 of the glass substrate 1 is preferably 5 nm or more, more preferably 10 nm or more, even more preferably 50 nm or more, even more preferably 100 nm or more, even more preferably 200 nm or more, particularly preferably 500 nm or more, and preferably 10,000 nm or less, more preferably 8,000 nm or less, even more preferably 5,000 nm or less, even more preferably 3,000 nm or less, and particularly preferably 2,000 nm or less. When the average length RSm in the uneven portion 2 of the glass substrate 1 is the above-mentioned lower limit value or more, the touch feeling of the surface of the glass substrate 1 and the writing feeling with a pen can be more effectively improved. Also, when the average length RSm in the uneven portion 2 of the glass substrate 1 is the above-mentioned upper limit value or less, the visibility of the image displayed on the surface including the uneven portion 2 of the glass substrate 1 can be more effectively improved.
[0060] In this embodiment, the maximum valley depth Rv in the uneven portion 2 of the glass substrate 1 is preferably 0.3 nm or more, more preferably 1 nm or more, even more preferably 10 nm or more, particularly preferably 50 nm or more, and preferably 10,000 nm or less, more preferably 8,000 nm or less, even more preferably 5,000 nm or less, even more preferably 3,000 nm or less, and particularly preferably 1,000 nm or less. When the maximum valley depth Rv in the uneven portion 2 of the glass substrate 1 is equal to or greater than the above lower limit, the touch feeling of the surface of the glass substrate 1 and the writing feeling with a pen can be more effectively improved. Also, when the maximum valley depth Rv in the uneven portion 2 of the glass substrate 1 is equal to or less than the above upper limit, the visibility of the image displayed on the surface including the uneven portion 2 of the glass substrate 1 can be more effectively improved.
[0061] When the average length RSm of the roughness curve element and the maximum valley depth Rv in the uneven portion 2 of the glass substrate 1 are within the above ranges, the resolution can be further increased when the glass substrate 1 is used in a display, and the writing comfort with a pen can be further effectively improved. In this case, the uneven portion 2 formed can more reliably suppress the occurrence of glare called sparkling caused by interference of scattered light.
[0062] The "average length RSm of the roughness curve element" and the "maximum valley depth Rv" are values obtained when the cutoff value of the high-pass filter λc for cutting off long wavelength components from the contour curve showing the cross-sectional shape of the uneven portion 2 of the glass substrate 1 is set to 14 μm, and the cutoff value of the low-pass filter λs for cutting off short wavelength components from the contour curve showing the cross-sectional shape of the uneven portion 2 is set to 0.35 μm.
[0063] The "average length RSm of roughness curve elements" is a parameter defined by JIS B0601:2001, and is a parameter that represents the average pitch between adjacent concave and convex portions in a contour curve that shows the cross-sectional shape of the concave-convex portion 2. Hereinafter, the "average length RSm of roughness curve elements" may be referred to as the "average length RSm".
[0064] Furthermore, "maximum valley depth Rv" is a parameter defined by JIS B0601:2001, and represents the depth of the deepest valley with respect to the average line in the contour curve showing the cross-sectional shape of the uneven portion 2. The above "average line" is a line obtained by replacing the curve showing the long wavelength components blocked by the high-pass filter λc with a straight line using the least squares method.
[0065] In addition, when the unevenness having the average length RSm of the roughness curve element is defined as the first unevenness, the uneven portion 2 of the glass substrate 1 may further have a second unevenness having an average length RSm of the roughness curve element larger than that of the first unevenness. More specifically, as shown in FIG. 3, the measured cross-sectional curve of the uneven portion 2 may have a first unevenness which is a minute unevenness and a second unevenness which is a large unevenness.
[0066] The average length RSm2 of the roughness curve elements of the second irregularity may be preferably 20 μm or more, more preferably 30 μm or more, and even more preferably 100 μm or more, and may be preferably 10,000 μm or less, more preferably 8,000 μm or less, and even more preferably 5,000 μm or less, 1,000 μm or less, or 500 μm or less.
[0067] The "average length RSm2 of the roughness curve element" is a value obtained when the cutoff value of the high-pass filter λc for cutting off long wavelength components from the contour curve showing the cross-sectional shape of the uneven portion 2 is set to a value four times the average length RSm of the roughness curve element of the second unevenness, and the cutoff value of the low-pass filter λs for cutting off short wavelength components from the contour curve showing the cross-sectional shape of the uneven portion 2 is set to 0.35 μm. The cutoff value of the high-pass filter λc of the second unevenness can be four times the value of the provisional average length RSm of the roughness curve element obtained when provisionally measuring without a filter. The "average length RSm2 of the roughness curve element" can be measured in accordance with JIS B0601:2001, similar to the average length RSm of the roughness curve element of the first unevenness. The "average length RSm2 of the roughness curve element" is the average of each periodic length Xs of the unevenness in a predetermined reference length.
[0068] The haze of the glass substrate 1 is not particularly limited and can be arbitrarily selected depending on the desired characteristics and purpose. When it is important to impart scattering properties or antiglare properties to the glass substrate 1 or to suppress the specular reflectance of the glass substrate 1, the haze of the glass substrate 1 is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more in the wavelength range of 380 nm to 780 nm, and is preferably 95% or less, more preferably 90% or less, and even more preferably 85% or less. When the haze of the glass substrate 1 is the above lower limit or more, the specular reflection of the glass substrate 1 can be further suppressed and the transmitted light can be further scattered. When the haze of the glass substrate 1 is the above upper limit or less, the transparency of the glass substrate 1 can be further improved.
[0069] On the other hand, when emphasis is placed on the transparency of the glass substrate 1, the haze of the glass substrate 1 is preferably 0.1% or more, more preferably 0.3% or more, even more preferably 0.5% or more, still more preferably 1% or more, and preferably 20% or less, more preferably 15% or less, and even more preferably 10% or less, in the wavelength range of 380 nm to 780 nm. When the haze of the glass substrate 1 is within the above range, the transparency of the glass substrate 1 can be further improved.
[0070] The non-processed portion 3 of the glass substrate 1 may not be subjected to any surface treatment at all, or may be subjected to a surface treatment different from that of the uneven portion 2. Examples of surface treatment different from that of the uneven portion 2 include blast treatment performed under conditions different from those of the uneven portion 2, coating with a component containing a SiO2 component, coating with a component containing fluorine, and surface treatment by HF etching. The non-processed portion 3 may be subjected to multiple surface treatments different from those of the uneven portion 2.
[0071] In addition, an anti-reflection film, an anti-soiling film, a decorative film, a decorative coating, or the like may be provided on the non-processed portion 3 of the glass substrate 1. In some cases, an anti-soiling film, a decorative film, a decorative coating, or the like may be provided on the uneven portion 2 of the glass substrate 1.
[0072] The anti-reflection film may be, for example, a dielectric multilayer film in which a low refractive index film and a high refractive index film are alternately laminated. The anti-reflection film may be formed by a sputtering method, a CVD method, or the like.
[0073] The antifouling film is a film for preventing fingerprints from adhering and imparting water repellency and oil repellency. The antifouling film preferably contains a fluorine-containing polymer containing silicon in the main chain. As the fluorine-containing polymer, for example, a polymer having a -Si-O-Si- unit in the main chain and a water-repellent functional group containing fluorine in the side chain can be used. The fluorine-containing polymer can be synthesized, for example, by dehydration condensation of silanol.
[0074] Examples of decorative films and decorative coatings include resins such as polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), polypropylene (PP), polyethylene terephthalate (PET), acrylic, urethane, and fluorine-based resins, metal foils, and laminates thereof.
[0075] The glass substrate 1 of this embodiment can be suitably used for displays, housings, doors, etc. of electronic devices. In particular, it can be suitably used as a cover member provided on the front of a display device such as a liquid crystal display. In this case, the glass substrate 1 may be used for a pen input device that allows input operations (pointing operations) of characters, figures, etc. to be performed using input means such as an input pen or a fingertip.
[0076] [Glass substrate manufacturing method] Next, an example of a method for manufacturing the glass substrate 1 will be described.
[0077] The uneven portion 2 of the glass substrate 1 can be formed, for example, by subjecting the surface of the original glass substrate to a process such as blasting. The blasting may be a wet blasting process or a sand blasting process. However, the blasting is preferably a wet blasting process.
[0078] Wet blasting is a process in which abrasive grains composed of solid particles such as alumina and liquid such as water are uniformly mixed to form a slurry, which is then sprayed at high speed from a spray nozzle using compressed air onto a workpiece made of an original glass substrate, thereby forming fine irregularities on the workpiece.
[0079] In wet blasting, when the slurry is sprayed at high speed and collides with the workpiece, the abrasive particles in the slurry scrape, hit, and rub the surface of the workpiece, forming fine irregularities on the surface of the workpiece.
[0080] In this case, the abrasive grains sprayed onto the workpiece and the pieces of the workpiece scraped off by the abrasive grains are washed away by the liquid sprayed onto the workpiece, so that fewer particles remain on the workpiece.
[0081] In wet blasting, when the slurry is sprayed onto the workpiece, the liquid carries the abrasive grains to the workpiece, making it easier to use finer abrasive grains than in dry sandblasting, and reducing the impact when the abrasive grains collide with the workpiece, making it possible to perform precise machining.
[0082] In the wet blasting process, the scanning pitch of the nozzle can be, for example, 50 μm or more and 10,000 μm or less. The number of times the nozzle scans (the number of times the same location is scanned) can be, for example, 1 time or more and 5 times or less. The moving speed of the nozzle (processing speed) can be, for example, 1 mm / s or more and 300 mm / s or less.
[0083] In the manufacturing method of this embodiment, the processing pressure during the blasting treatment is 0.1 MPa or more and 3.0 MPa or less. The processing pressure during the blasting treatment is preferably 0.2 MPa or more, more preferably 0.3 MPa or more, even more preferably 0.35 MPa or more, even more preferably 0.4 MPa or more, preferably 2.8 MPa or less, and more preferably 2.7 MPa or less. The processing pressure during the blasting treatment is the injection pressure of the slurry.
[0084] In the manufacturing method of this embodiment, the processing pressure during the blasting treatment is equal to or higher than the above-mentioned lower limit, which makes it easier to compound particles containing at least one selected from the group consisting of Al, Zr, and Si in the unevenness 2 of the obtained glass substrate 1. Furthermore, when the processing pressure during the blasting treatment is equal to or lower than the above-mentioned upper limit, microcracks are even less likely to occur in the obtained glass substrate 1.
[0085] The concentration of the abrasive grains in the slurry is preferably 1 mass % or more, more preferably 2 mass % or more, and even more preferably 2.5 mass % or more, and is preferably 30 mass % or less, more preferably 27 mass % or less, and even more preferably 25 mass % or less. When the concentration of the abrasive grains in the slurry is within the above range, it becomes easier to compound particles containing at least one selected from the group consisting of Al, Zr, and Si in the uneven portion 2 of the obtained glass substrate 1.
[0086] As the abrasive grains, particles containing at least one selected from the group consisting of Al, Zr, and Si described above can be used.
[0087] The Mohs hardness of the abrasive grains is preferably 4 or more, more preferably 4.5 or more, and even more preferably 5 or more. In this case, stronger grip can be imparted to the uneven portion 2 of the obtained glass substrate 1, and the feel of the surface of the glass substrate 1 and the feel of writing with a pen can be more effectively improved. The upper limit of the Mohs hardness of the abrasive grains is not particularly limited, and can be, for example, 10.
[0088] Examples of the shape of the abrasive grains include angular, acicular, polyhedral, crushed, irregular, substantially spherical, etc. Among them, the abrasive grains are preferably polyhedral in shape, from the viewpoint of providing a stronger grip on the uneven portion 2 of the obtained glass substrate 1 and facilitating compounding of particles with the uneven portion 2 of the glass substrate 1.
[0089] The purity of the abrasive grains is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. When the purity of the abrasive grains is equal to or more than the above lower limit, the transparency of the concave-convex portion 2 of the obtained glass substrate 1 can be further improved. Therefore, the purity of the abrasive grains may be 100%. The purity of the abrasive grains is the purity of at least one element selected from the group consisting of Al, Zr, and Si.
[0090] Average particle size of abrasive grains D 50is preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.3 μm or more, and is preferably 10 μm or less, more preferably 9 μm or less, even more preferably 8 μm or less. 50 When the thickness is within the above range, the feel of the surface of the obtained glass substrate 1 to the touch and the feel of writing with a pen can be more effectively improved.
[0091] Furthermore, in the manufacturing method of this embodiment, the arithmetic mean height Sa and maximum valley depth Rv of the uneven portion 2 of the glass substrate 1 can be increased by increasing the grain size of the abrasive grains in the wet blasting process, increasing the concentration of the slurry, increasing the processing pressure, slowing down the nozzle movement speed, or increasing the number of nozzle scans.
[0092] In addition, the average length RSm of the roughness curve elements in the uneven portion 2 of the glass substrate 1 can be reduced by reducing the grain size of the abrasive grains in the wet blasting process, decreasing the slurry concentration, reducing the processing pressure, and increasing the nozzle scanning speed.
[0093] In the manufacturing method of this embodiment, it is preferable to perform a heat treatment on the original glass substrate that has been subjected to the blasting treatment. In this case, the particles can be more firmly combined with the uneven portion 2 of the obtained glass substrate 1. This makes it possible to prevent the particles from falling off over time or peeling off due to friction, and to obtain a glass substrate 1 that has a stable and excellent surface feel and writing comfort with a pen.
[0094] The heat treatment temperature of the original glass substrate can be, for example, 100° C. or more and the glass transition temperature or less of the original glass substrate. The heat treatment temperature of the original glass substrate is preferably 120° C. or more, more preferably 130° C. or more, and preferably 550° C. or less, more preferably 500° C. or less.
[0095] The heat treatment time of the original glass substrate can be, for example, 10 minutes or more and 24 hours or less. The heat treatment of the original glass substrate can be performed, for example, in an air atmosphere.
[0096] The present invention will be described in more detail below with reference to specific examples. The present invention is not limited to the following examples, and can be modified as appropriate within the scope of the present invention.
[0097] (Examples 1 to 6) First, an aluminosilicate glass plate (manufactured by Nippon Electric Glass Co., Ltd., 50 mm square, thickness: 0.5 mm) was prepared as an original glass substrate.
[0098] Next, a wet blasting process was performed on one main surface of the prepared original glass substrate to form a concave-convex portion. The wet blasting process was performed by using a slurry prepared by uniformly mixing abrasive grains and water, and spraying the slurry from a nozzle using air to scan the processing stage on which the glass substrate was placed while moving the nozzle at a speed of 20 mm / s (scanning pitch: 0.5 mm).
[0099] In Examples 1 to 6, α-alumina particles (purity 96%) were used as the abrasive grains. Pure water with a pH of 7 was used as the water. In addition, in the wet blasting treatment in Examples 1 to 6, the slurry injection pressure as the treatment pressure and the concentration of the abrasive grains in the slurry (slurry concentration) are as shown in Tables 1 and 2 below.
[0100] In Examples 1 to 5, the original glass substrate after the wet blasting treatment was washed with pure water, and then the original glass substrate was subjected to a heat treatment at 120° C. for 30 minutes to obtain a glass substrate. On the other hand, in Example 6, the original glass substrate after the wet blasting treatment was not subjected to a heat treatment and was used as a glass substrate as it was.
[0101] (Examples 7 and 8) Except for using zirconium oxide particles (purity 93%) as the abrasive grains and changing the slurry injection pressure as the treatment pressure and the concentration of the abrasive grains in the slurry (slurry concentration), glass substrates were obtained in the same manner as in Example 1. In addition, in the wet blasting treatments in Examples 7 and 8, the slurry injection pressure as the treatment pressure and the concentration of the abrasive grains in the slurry (slurry concentration) are as shown in Table 3 below.
[0102] (Examples 9 and 10) Except for using silicon oxide particles (purity 96%) as the abrasive grains and changing the slurry injection pressure as the treatment pressure and the concentration of the abrasive grains in the slurry (slurry concentration), glass substrates were obtained in the same manner as in Example 1. In addition, in the wet blasting treatments in Examples 9 and 10, the slurry injection pressure as the treatment pressure and the concentration of the abrasive grains in the slurry (slurry concentration) are as shown in Table 4 below.
[0103] Comparative Example 1 An aluminosilicate glass plate (manufactured by Nippon Electric Glass Co., Ltd., 50 mm square, thickness: 0.5 mm) serving as the original glass substrate was used as it was without being subjected to wet blasting treatment.
[0104] Comparative Example 2 The slurry prepared in the same manner as in Example 1 was applied to one main surface of an original glass substrate prepared in the same manner as in Example 1, and the original glass substrate to which the slurry was applied was then subjected to a heat treatment at 450° C. for 30 minutes to obtain a glass substrate.
[0105] Comparative Example 3 An etching treatment was carried out with ammonium hydrogen fluoride on one main surface of an original glass substrate prepared in the same manner as in Example 1 to form projections and recesses, thereby obtaining a glass substrate.
[0106] [Evaluation method] (Evaluation of surface roughness of glass substrate) The arithmetic mean height Sa was measured for the uneven portions (processed portions) of the glass substrates obtained in Examples 1 to 10 and Comparative Examples 2 and 3. The arithmetic mean height Sa was also measured for the surface of the glass substrate of Comparative Example 1. The results are shown in Tables 1 to 4 below.
[0107] The arithmetic mean height Sa was measured using a white light interference microscope manufactured by Zygo (product name: NewView7300).
[0108] The measurement conditions were a 50x objective lens and a 2x zoom lens, and the arithmetic mean height Sa was measured over a measurement area of 74μm×55μm, with a camera pixel count of 640×480 and an accumulation count of 10. The cutoff value of the high-pass filter λc when measuring the arithmetic mean height Sa of the uneven portion (surface) was set to 14μm, and the cutoff value of the low-pass filter λs was set to 0.35μm.
[0109] (Observation of the surface of a glass substrate) The surfaces of the glass substrates of Examples 1 to 10 and Comparative Examples 1 to 3 were observed by a scanning electron microscope. The scanning electron microscope used was a model "S3400" manufactured by Hitachi High-Technologies Corporation. The measurement was performed at a magnification of 1000 times.
[0110] Fig. 4 is a scanning electron microscope photograph showing the uneven portion of the glass substrate of Example 4. Fig. 5 is a scanning electron microscope photograph enlarging the portion in Fig. 4 where the alumina particles are provided. Fig. 6 is a scanning electron microscope photograph showing the surface of the glass substrate of Comparative Example 1. Fig. 7 is a scanning electron microscope photograph showing the uneven portion of the glass substrate of Comparative Example 3.
[0111] As shown in Figures 4 and 5, alumina particles are composited in the uneven portion (processed portion) of the glass substrate of Example 4. On the other hand, as shown in Figure 6, alumina particles are not present on the surface of the glass substrate of Comparative Example 1. Moreover, as shown in Figure 7, alumina particles are not present in the uneven portion (processed portion) of the glass substrate of Comparative Example 3 either.
[0112] Similarly, it was confirmed that alumina (Al2O3) particles were composited in the uneven portion (processed portion) of the glass substrate in Examples 1 to 3, 5, and 6. Furthermore, it was confirmed that zirconium oxide (ZrO2) particles were composited in the uneven portion (processed portion) of the glass substrate in Examples 7 and 8, and that silicon oxide (SiO2) particles were composited in the uneven portion (processed portion) of the glass substrate in Examples 9 and 10. Furthermore, in the glass substrate in Comparative Example 2, alumina particles were present in the uneven portion (processed portion) of the glass substrate, but composite of the alumina particles was not observed. In addition, in the scanning electron microscope photograph, the portion where the concentration of Al was 90 mass% or more was determined as the portion where alumina particles existed, the portion where the concentration of Zr was 90 mass% or more was determined as the portion where zirconium oxide particles existed, and the portion where the concentration of Si was 90 mass% or more was determined as the portion where silicon oxide particles existed.
[0113] Furthermore, the average particle size of each particle observed in Examples 1 to 10 and Comparative Example 2 was measured using image analysis software (Software included with S3400 SEM-EDX, manufactured by Hitachi High-Tech Corporation). The results are shown in Tables 1 to 4 below.
[0114] In addition, the total mass ratio of Al, Zr, and Si in a 100 μm square area was determined at five arbitrary locations on the uneven and non-processed portions of the glass substrates of Examples 1 to 10 and Comparative Example 2 by scanning electron microscope energy dispersive X-ray spectroscopy (SEM-EDX, Hitachi High-Tech Corporation, product number "S3400"), and the average value was taken as the total mass ratio of Al, Zr, and Si in the uneven and non-processed portions. The difference in the total mass ratio of Al, Zr, and Si in the uneven and non-processed portions was calculated from the difference between the total mass ratio of Al, Zr, and Si in the uneven and non-processed portions and the total mass ratio of Al, Zr, and Si in the uneven and non-processed portions. The results are shown in Tables 1 to 4 below.
[0115] (Evaluation of touch and writing comfort) The touch and writing comfort were evaluated for the uneven portions (processed portions) of the glass substrates of Examples 1 to 10 and Comparative Examples 2 and 3. The touch and writing comfort were also evaluated for the surface of the glass substrate of Comparative Example 1. The results are shown in Tables 1 to 4 below.
[0116] Sensory evaluation of the tactile feel and writing comfort was performed by 10 subjects of different ages and genders, and the evaluation was based on the following criteria. The tactile feel was evaluated by touching the evaluation target directly with a finger. The writing comfort was evaluated by writing characters on the evaluation target with a commercially available stylus pen.
[0117] <Evaluation criteria> 5: More than 8 out of 10 people felt a sense of discomfort 4: 6 to 7 out of 10 people felt a sense of discomfort 3: 5 out of 10 people felt a sense of discomfort 2: 6 to 7 out of 10 people felt that there was no sense of grip. 1: More than 8 out of 10 people felt no grip or had some other sensation.
[0118] In addition, a durability test was conducted on the glass substrates of Examples 1 to 10 and Comparative Example 2, and a touch evaluation was conducted before and after the durability test. This was used to evaluate whether there was a change in the touch evaluation before and after the durability test. The durability test was conducted by placing a weight of 500 g on a piece of gauze measuring 25 mm x 25 mm, and moving the weight back and forth over the uneven portion of the glass substrate 500 times at a friction speed of 100 mm / s.
[0119] [Table 1]
[0120] [Table 2]
[0121] [Table 3]
[0122] [Table 4]
[0123] As is clear from Tables 1 to 4, the glass substrates of Examples 1 to 10 had a strong grip at the uneven parts, and it was confirmed that the surface feel and writing comfort with a pen were effectively improved. In particular, the glass substrates of Examples 1 to 5 and 7 to 10, which were subjected to heat treatment, showed no change even after the durability test, and were confirmed to have excellent surface feel. On the other hand, the glass substrates of Comparative Examples 1 to 3 could not sufficiently improve the surface feel and writing comfort with a pen. [Explanation of symbols]
[0124] 1,10...Glass substrate 1a...First main surface 1b…Second main surface 2...Uneven part 3…Unprocessed part
Claims
1. A glass substrate having a concave-convex portion on a surface thereof and a non-processed portion that is not processed to provide the concave-convex portion, the concave-convex portion has an arithmetic mean height Sa of 1 nm or more and 100 nm or less in a 74 μm×55 μm region when the cutoff value of the high-pass filter λc is 14 μm and the cutoff value of the low-pass filter λs is 0.35 μm; The uneven portion contains at least one component selected from the group consisting of Al, Zr, and Si, a difference between the total mass ratio of Al, Zr, and Si in any 100 μm square area of the uneven portion and the total mass ratio of Al, Zr, and Si in any 100 μm square area of the non-processed portion is 0.1 mass % or more.
2. A glass substrate having a concave-convex portion on a surface thereof and a non-processed portion that is not processed to provide the concave-convex portion, the concave-convex portion has an arithmetic mean height Sa of 1 nm or more and 100 nm or less in a 74 μm×55 μm region when the cutoff value of the high-pass filter λc is 14 μm and the cutoff value of the low-pass filter λs is 0.35 μm; A glass substrate, wherein particles containing at least one of Al, Zr, and Si are compounded in the uneven portion.
3. The glass substrate according to claim 1 , wherein both the concave-convex portion and the non-processed portion are provided on one main surface of the glass substrate.
4. the glass substrate has a first main surface and a second main surface opposed to each other; The uneven portion is provided on the first main surface of the glass substrate, The glass substrate according to claim 3 , wherein the unprocessed portion is provided on the second main surface of the glass substrate.
5. 3. The glass substrate according to claim 1, wherein a difference between a total mass ratio of Al, Zr, and Si in any 100 μm square area of the uneven portion and a total mass ratio of Al, Zr, and Si in any 100 μm square area of the non-processed portion is 10 mass% or less.
6. The glass substrate according to claim 1 , wherein the glass substrate is made of silicate glass.
7. 3. The glass substrate according to claim 2, wherein the particles are at least one type of particles selected from the group consisting of aluminum oxide, aluminum nitride, aluminum carbide, aluminum silicate, zirconium oxide, yttria-stabilized zirconia, zircon, silicon oxide, and silicon nitride.
8. 3. The glass substrate according to claim 2, wherein the particles have an average particle size of 0.1 μm or more and 10 μm or less.
9. The glass substrate according to claim 2 , wherein the purity of the particles is 90% or more.
10. A method for producing a glass substrate according to claim 1 or 2, comprising the steps of: preparing an original glass substrate; A step of subjecting the original glass substrate to a blasting treatment; Equipped with The method for producing a glass substrate, wherein a treatment pressure during the blast treatment is 0.1 MPa or more and 3.0 MPa or less.
11. The method for manufacturing a glass substrate according to claim 10 , further comprising a step of subjecting the original glass substrate that has been subjected to the blasting treatment to a heat treatment.
12. The method for producing a glass substrate according to claim 11, wherein the heat treatment temperature is 100° C. or higher and a glass transition temperature of the original glass substrate or lower.
Citation Information
Patent Citations
Pen input device, glass substrate for pen input device and manufacturing method thereof
JP2018020942A